Influence of incremental ECAP on the microstructure and tensile behaviour of commercial purity titanium. (2017) - Qarni, Muhammad Jawad; Rosochowski, Andrzej; Boczkal, Sonia
Abstract: Severe plastic deformation (SPD) is an effective method for producing ultrafine grained (UFG) structures in metals. UFG materials are characterized by an average grain size of <1 µm and mostly high angle grain boundaries. These materials exhibit exceptional improvements in strength, superplastic behaviour and in some cases enhanced biocompatibility. Among various SPD methods available, equal channel angular pressing (ECAP) is the most effective method for obtaining bulk UFG billets. Lately, the interest is towards industrialization of the ECAP technique to enable processing of very long or continuous billets. Incremental ECAP (I-ECAP) developed at University of Strathclyde, offers such possibility. The present work details the processing of commercial purity titanium (CP-Ti), using I-ECAP process, with the objective of improving its strength characteristics. CP-Ti billets were successfully processed for up to four passes at 300 °C using an I-ECAP die with a channel angle of 90°. Electron backscatter diffraction (EBSD) technique was used to characterize the microstructure after first and fourth pass of the process. Analysis of the first pass sample revealed heterogeneous structure with a mixture of elongated and refined equi-axed grains. Moreover, existence of 10 1 ¯ 2 tensile twinning in the microstructure was also observed. Remarkable refinement was achieved after fourth pass and ultrafine-grain (UFG) structure was successfully achieved. Room temperature tensile tests carried out on unprocessed and UFG material, display the improvement in strength. The yield strength of the processed material was increased from 308 to 671 MPa and the ultimate tensile strength from 549 to 730 MPa. However, strain-hardening ability of the material was greatly reduced because of processing. Consequently, the material suffers loss in ductility, from 31.9% elongation to failure in the unprocessed form to 21.1% in UFG form. Finally, fracture morphology of the unprocessed and processed CP-Ti displays characteristics of ductile failure. It has been shown that I-ECAP is an effective method for improving strength characteristics of CP-Ti.